Peculiarities of the stress-strain state of thin plates in the framework of the theory of micropolar elasticity - Sargsyan, Samvel Hoganesovich (Computational Continuum Mechanics, 2009)
The aim of the present paper is to investigate the bending problems for hinge-supported rectangular and circular plates. The study is carried out using three general mathematical models of micropolar elasticity, namely, models with independent displacement and rotation fields, constraint rotation, low shear rigidity. Analytical solutions are presented for quantities defining the stress-strain state of micropolar plates. Numerical analysis of these solutions reveals some distinctive features of the stress-strain state of micropolar plates.
Keywords: micropolar elasticity; stress-strain state; thin plates